Criminal Acts of Threats by Debt Collectors Against Debtors in the Per-spective of the Criminal Code and Islamic Criminal Law - Ahmad Assyura, Afifuddin Salim; Mukhsin, Abd. (LEGAL BRIEF, 2024)
Criminal acts of threats by debt collectors against debtors are a significant issue in the context of criminal law in Indonesia. This study aims to analyze legal provisions regarding criminal acts of threats in the Criminal Code (KUHP) and from the perspective of Islamic criminal law. The research method used includes literature studies and case analysis. The results show that although the KUHP provides a comprehensive legal framework, its implementation is often ineffective due to weak oversight and law enforcement. Islamic criminal law offers a rigid approach but requires adaptation to modern legal contexts. Evaluations of threat cases by debt collectors reveal significant violations and insufficient protection for debtors. Recommendations for improvement include drafting more detailed regulations, enhancing oversight, and comprehensive legal education. The implementation of digital technology in debt collection is also suggested to increase transparency and accountability.